A perfect day [videorecording (DVD)] - León, Fernando, 1968-; Toro, Benicio del, 1967-; Robbins, Tim, 1958-; Kurylenko, Olga, 1979-; Farias, Paula, 1968- (IFC Films, 2016)
It's just another day on the job for a band of badass combat zone rescue workers as they defy death and confront war's absurdities. The setting is 1995, somewhere in the Balkans. Over the course of 24 breathless hours, Mambru leads his team of humanitarians, including hard-bitten, wisecracking veteran B and new recruit Sophie, as they deal with a most unexpected crisis, layers of bureaucratic red tape, and the reappearance of Mambru's old flame.